Literasi Ekologi Masyarakat Terhadap Konservasi Mata Air Senjoyo di Desa Tegalwaton Kabupaten Semarang (Jurusan Geografi, Fakultas Ilmu Sosial, Universitas Negeri Semarang, 2023)
Pitayati, Ayu. 2022, Community Ecological Literacy on Senjoyo Spring Conservation in Tegalwaton Village, Semarang Regency. Geography Department, Faculty of Social Sciences, Universitas Negeri Semarang. Advisor, Dr. Hariyanto, M.Si. Keywords: Ecological Literacy, Conservation, Senjoyo Springs Senjoyo Spring is one of the springs in Semarang Regency. Senjoyo Springs have a very important role. The various uses do not rule out the possibility of impacts on the sustainability of the existing ecosystems in the Senjoyo Springs Area. The condition of Senjoyo Springs is currently maintained and sustainable, but there are still some ecological problems such as there is still a lot of garbage found and the unavailability of waste water treatment before it is released. Research objectives 1.) to find out the efforts made by the Tegalwaton Village community for water conservation 2.) to analyze ecological literacy of the community's efforts to conserve Senjoyo Springs. The location of this research is in Jubug Hamlet, Tegalwaton Village, Semarang Regency. The variables of this study are ecological literacy and conservation efforts. The population used in this study were heads of families in Jubug Hamlet with a total sample of 69 heads of families. The sampling technique used is proportional random sampling technique. Data collection techniques using interviews, observation, questionnaires, tests and documentation. Quantitative descriptive analysis technique and crosstab analysis technique (cross tabulation). The results of this study indicate that the community's conservation efforts for Senjoyo Springs are also at very high criteria. Efforts made by the Tegalwaton Village community are by forming the POKDARWIS organization, carrying out reforestation, cleaning the spring area, not cutting down trees in the spring area, utilizing the flow of water from the spring for washing, bathing and not throwing garbage in the Senjoyo Spring area. Community ecological literacy consisting of environmental knowledge, attitudes towards the environment, cognitive skills and pro-environmental behavior is at very high criteria. When connected with the level of education, it is directly proportional to the level of public awareness, the higher the knowledge a person has, the more awareness a person has in protecting the environment from damage. Apart from the educational factor, this spring is a vital spring for the community, so that the community is aware of the importance of maintaining the existence of Senjoyo Spring. The advice given to the community and stakeholders is to continue to increase conservation efforts for the Senjoyo Springs by preserving local wisdom (dawuhan ceremony) for the younger generation, reforestation, not cutting down trees, not throwing garbage into the Senjoyo Springs area and conducting socialization to all levels of society. regarding the conservation of Senjoyo Springs.